(untitled) (European Journal of Biomedical Research, 2022)
Background: The current pandemic outbreak of COVID-19 due to the SARS-CoV-2 virus affected the health care systems, health services and economy globally. It also affected the health of the population worldwide, with high mortality and morbidity rates. The present study aimed to study the patients that were admitted to a tertiary care hospital and to investigate the potential correlation between hospitalization and RT-PCR for SARS-CoV-2 results with demographic characteristics and clinical characteristics. Moreover, it aimed to examine a mathematical formula that might describe the correlation of the aforementioned parameters. Methods: The study population included 1244 patients admitted to the Nikea General Hospital "Agios Panteleimon", Piraeus, Greece. Patient age, gender, underlying diseases, travel history, symptoms, etiology for hospital admission and contact with confirmed cases were recorded. Potential correlation of hospitalization and RT-PCR for SARS-CoV-2 results with the aforementioned characteristics were identified by chi-square test of independence and logistic regression analysis. Results: We observed significant correlation of hospitalization with fever, cough, dyspnea, pneumonia, travel history and etiology for hospital admission. We observed significant correlation of RT-PCR for SARS-CoV-2 results with rapid antigen test result, hospitalization etiology for hospital admission and contact with confirmed COVI-19 case. Conclusions: According to the logistic regression model, RT-PCR for SARS-CoV-2 result, fever, dyspnea, pneumonia, and underlying disease are the most important predictors for hospitalization in the population under study. Contact with confirmed COVID-19 case is the most important predictor for RT-PCR for SARS-CoV-2 result.